A Study on the Mechanical and Forming Performance of Oil Palm Fiber Reinforced Polypropylene Composite - Sivakumar, Dhar Malingam; Subramonian, Sivarao; Selamat, Mohd Zulkefli; Radzai, Said (American-Eurasian Journal of Sustainable Agriculture, 2014)
Composite materials have steadily gained recognition worldwide for its uses in various sectors such as aerospace, infrastructures and automotive industries. Natural fibers are gaining recognition as a substitute to synthetic fibers due to its recyclability and abundance. Palm fiber reinforced polypropylene composite panels have potential to be stamp formed in order to build complex geometries. In stamp forming the most sensitive feature is elastic recovery during unloading. This phenomenon will affect the net dimension of the final product. Objective: To identify the effects of forming rate, tool radius, temperature and ratio of fiber to polypropylene on the spring-back of palm fiber composite. To deduce an empirical model in predicting spring-back. To investigate the effect of fiber composition on its tensile strength. Results: Statistical analysis conducted shows all the studied parameters gives significant effect towards spring-back. The higher the temperature, feed rate and fiber composition (up to 30wt %) the smaller the spring-back and it is vice versa for tool radius. An empirical model was formulated to predict the spring-back angle. 30wt% of fiber composition was found to give the highest tensile strength. Conclusion: The suggested temperature, fiber composition, tool radius and feed rate to get the smallest spring-back angle in the current study are 150 °C, 30wt%, 2mm and 500mm/min. While the fiber composition of 30wt% shows the highest tensile strength.